Gestión administrativa y su incidencia en el servicio al cliente en la empresa almaquint s.a. Sección hotelería, cantón Quevedo, año 2014 - Mueckay Peñafiel, Gina Yorlay (2015)
This research project has as main objective to know "ADMINISTRATIVE AND ITS IMPACT ON CUSTOMER SERVICE IN THE COMPANY ALMAQUINT SA SECTION hotels, Quevedo Canton, 2014.‖ To develop the aforementioned title, consideration was given to the program organization that maintains the company, and its impact on economic development, influencing the efficiency of the service offered by the company, in order to determine the importance of administrative management in the quality of service to users and to maintain its position. Identifying the incidence of customer service in the development of the company, considering that proper management and a successful organization are instigating success in business, concern arose to describe the administrative process to know the importance of it as a strategic tool that must be considered by the institution, to achieve high levels of profitability and above all improve their service and commercial participation. We conclude that you must use the strategic plan of the company in order that this allows us to detect errors present in order to take the necessary corrective measures that would benefit the institution so that resources are optimized. The company is recommended to foster communication with all staff and it is they who guide….